CrossTalk opposing view: Heat acclimatization does not improve exercise performance in a cool condition - Nybo, L.; Lundby, CV. (The Journal of Physiology, 2016)
It is clear that heat acclimatization markedly improves endurance performance in hot environments (Sawka et al. 1985; Nielsen et al. 1993; Racinais et al. 2015), but the idea that physiological adaptations achieved via heat acclimatization will also transfer to improved performance in cooler environments is questionable. Except from studies suffering from the lack of a matched control group, only one recent study, by Lorenzo et al. (2010), provides evidence for a transfer effect, as the authors report remarkable improvements in maximal oxygen consumption and ergometer time trial performance in both hot and cool conditions following 10 days of heat acclimation training. In that study acclimation was achieved through 90 min of additional training per day conducted in climatic heat chambers combined with maintenance of the participants` habitual training (volume or intensity not reported or quantified). In contrast we observe no change in outdoor bicycle or laboratory ergometer time trial performance, peak power output during incremental indoor cycling, or maximal oxygen consumption when endurance trained cyclists are tested in cool conditions following either 10 days of indoor heat acclimation (Keiser et al. 2015), i.e. similar to the approach used by Lorenzo et al. (2010), or after 14 days of outdoor natural dry heat acclimatization (Karlsen et al. 2015).However, both regimes did facilitate improvements in time trial performance when conducted in the heat and were fully compatible with those reported to occur in the heat by Lorenzo et al. (2010). Furthermore, the sudomotor and cardiovascular adaptations were similar to the physiological heat acclimatization effects reported in studies of similar duration (Nielsen, 1998; Racinais et al. 2012; Taylor, 2014).